DEVELOPMENT OF RESPONSIVE AND INTERACTIVE MOBILE-BASED REALISTIC MATHEMATICS LEARNING APPLICATION WITH EXTREME PROGRAMMING SYSTEM METHOD - Prananda, Dimas Adi; Imanda, Rahmi; Anhari, Tirta; Sulaeman, Mia Kamayani; Rizkiawan, M. Asep (STKIP PGRI Tulungagung, 2025)
This research has the main objective of producing a product of mathematics learning application design that supports the mathematics learning process to be more qualified. The application developed can help teachers to map the competencies and learning achievements of each student. In supporting the development of this application also combines realistic mathematics and quizzes that are designed to be interactive and responsive. In directing this research, the object-oriented extreme programming system development method was developed through the stages of planning, design, coding and testing. With this application, teachers are greatly helped in organizing students in a more qualified and interactive learning process. Based on the results of testing that has been done in the classroom, the response of teachers and students with this application gets a very positive response